2001
DOI: 10.1046/j.1471-4159.2001.00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of unaggregated and aggregated amyloid β protein (1–40) on K+ channel currents in primary cultures of rat cerebellar granule and cortical neurones

Abstract: The effects of amyloid b protein on voltage-gated K 1 channel currents were studied using the whole-cell patch-clamp technique. The 1±40 amino acid form of amyloid b protein was applied to primary cultures of rat cerebellar granule and cortical neurones for 24 h. Both the unaggregated and aggregated forms of the peptide, which have differing biological activities, were used. In cerebellar granule neurones, 24-h pre-incubation with 1 mM unaggregated amyloid b protein resulted in a 60% increase in the`A'-type co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 48 publications
2
51
0
2
Order By: Relevance
“…21 While Aβ is commonly thought of as the main toxic agent in AD, there is emerging evidence of a normal physiological role for the peptide in the regulation of neuronal calcium and potassium channel currents. 22,23 This, therefore, indicates that Aβ should only be considered as a toxic agent when levels increase as a result of an imbalance in its production and degradation/ clearance, such as occurs in AD.…”
Section: Regulates the β-Secretase Cleavage Of Appmentioning
confidence: 99%
“…21 While Aβ is commonly thought of as the main toxic agent in AD, there is emerging evidence of a normal physiological role for the peptide in the regulation of neuronal calcium and potassium channel currents. 22,23 This, therefore, indicates that Aβ should only be considered as a toxic agent when levels increase as a result of an imbalance in its production and degradation/ clearance, such as occurs in AD.…”
Section: Regulates the β-Secretase Cleavage Of Appmentioning
confidence: 99%
“…Recent research has demonstrated that changes in K ϩ channel activity play a major pathogenetic role in many neurodegenerative disorders, including Alzheimer's disease (AD). In fact, ␤-amyloid fragments (A␤), generated upon processing of the integral membrane amyloid precursor protein (Suh and Checler, 2002), alter the properties of K ϩ currents in mammalian neurons (Jalonen et al, 1997;Yu et al, 1998;Jhamandas et al, 2001;Ramsden et al, 2001;Pannaccione et al, 2005). Furthermore, a study performed on SN56 cells, a cholinergic cell line from rat, reported that treatment with A␤ increased the amount of delayed rectifier K ϩ currents and increased cell death (Colom et al, 1998).…”
Section: Alteration Of Neuronal Kmentioning
confidence: 99%
“…Ramsden et al (2001) noted that longterm exposure of rat cerebellar granule neurons to unaggregated A␤ 1-40 led to an increase in both the inactivating I KA current (peak-end current) and I KV (end current), whereas acute administration had no effect. Increased current was also observed using a protocol employing a Ϫ50 mV prepulse, which removes the majority of the I KA current component.…”
mentioning
confidence: 99%